Pung Practices among the Gurung – An Anthropological Perspective - Gurung, Shanti (Shahid Kirti Multidisciplinary Journal, 2023)
This article penetrates the Gurung pre-wedding ritual 'Pung' which is taken as the confirmation of marriage between the bride and grooms. The study of 'Pung' practices among the Gurung is one of the anthropological study which has not done any study yet through anthropological lens. Pung itself is one of the mandatory and strongest pre-wedding rituals of Gurung. This practice does not only tie the relationship among the two families but also consolidates the relationship among the Gurungs. After the Pung bride can make a choice of her stay and can move from parent's home even after having kids too. This study has been implemented through the ethnographic examination through participation, observation, and interview and questionnaire method with the Gurungs of Gorkha and Lamjung who have been living in Kathmandu. In this study, eleven respondents including five women, five men, one Klepri (the Gurung priest), one Jaisi (the Gurung fortune teller) and one politician (former village development committee chair person) were taken as a key informants by using convenient method and interview and observations were taken as a research design tool. Interviews show that 'Pung' rituals are one of the mandatory formalities to be done before wedding. According the key informants they do not remember exact date of the practices about 'Pung' rituals. They even do not know how and who created those divisions of caste hierarchy among the Gurungs but have been following this ritual since they know. This ritual is also taken as the marriage itself (informal) and also opens for sexual intercourse, staying together in the same house and flexibility for the procurement.